Linkages between Social Media Presence, Brand Awareness, Customer Loyalty, and Sales Growth in Entrepreneurial Companies (Study on Fashion Industry Entrepreneurs in West Java) - Frans Sudirjo; Andry Stepahnie Titing; Yokie Radnan; Hefri Yodiansyah; Bambang Bambang (Westscience Press, 2023)
This study aimed to investigate the relationship between social media presence, brand awareness, customer loyalty, and sales growth among fashion industry entrepreneurs in West Java. A survey was conducted with 150 participants, and the data were analyzed using Pearson’s correlation coefficient. The results indicate that social media presence is positively associated with brand awareness, customer loyalty, and sales growth. The findings suggest that fashion industry entrepreneurs in West Java should focus on building and maintaining a solid social media presence to improve their brand awareness, customer loyalty, and sales growth.